Answer: just use PEMDAS
[(30+6) -3'2] / 9'2
= (36 -9)/ 9'2
= 27/9'2
= 3'2
= 6
Step-by-step explanation:
section?
A a point and a triangle
B a plane and a cone
C a circle and a square
D a line and a
Answer:
A
Step-by-step explanation:
I did this before and I got it correct
Answer:
The burger is $5 each.
Step-by-step explanation:
8x = 40
x = 5
Answer:
the unit price would be $5
Step-by-step explanation:
40÷8=5
5×8=40
The required cost per person at the party is given as $15.
The process in mathematics to operate and interpret the function to make the function or expression simple or more understandable is called simplifying and the process is called simplification.
Here,
John threw a surprise birthday party for his friend.
Let the cost per peroson be c,
According to the question,
32c = 480
c = 480 / 32
c = 15
Thus, the required cost per person at the party is given as $15.
Learn more about simplification here:
#SPJ2
Answer:
Step-by-step explanation:
According to the following pattern sequence ( ), it is Arithmetic Sequence, because every negative number is subtracted by . So, to find the 24th term, you need to use the Arithmetic Sequence Formula and solve to find the 24th term:
: nth term in the sequence
: 1st term
: term position
: Common difference
-Apply to the formula:
-Solve:
Therefore, the 24th term is .
The nth term of the sequence is given by the formula nth term = -1 + (n-1)(-3), resulting in a24 (the 24th term) being -70.
To find the nth term of any arithmetic sequence, you can use the formula: nth term = a + (n - 1)d where a is the first term and d is the common difference. In the given sequence -1, -4, -7, -10, the first term (a) is -1 and the common difference (d) is -3 (because each term is 3 less than the previous term).
So, the nth term formula for this sequence would be
nth term = -1 + (n-1)(-3)
To find the 24th term of the sequence (a24), you would substitute n with 24. So, a24 = -1 + (24-1)(-3) = -70.
#SPJ2
The equation used to solve this problem is this:
H(t) = -16t^2 +vt + s
Where,
H(t) is the distance of the ball from the ground in feet,
t is the time in seconds,
v is the initial velocity of the ball as it is thrown up in feet/sec,
s is the distance of the ball from the ground when it was thrown in feet
Plugging in the given values,
0 = 16 t^2 + 35t + 0
This is a quadratic equation and the roots are:
0 and 2.19
answer: 2.19 seconds